Chromosome Painting Based on Bulked Oligonucleotides in Cotton - Liu, Yuling; Wang, Xiuyuan; Wei, Yangyang; Liu, Zhen; Lu, Quanwei; Liu, Fang; Zhang, Tao; Peng, Renhai (Frontiers in Plant Science, 2020)
Chromosome painting is one of the key technologies in cytogenetic research, which can accurately identify chromosomes or chromosome regions. Oligonucleotide (oligo) probes designed based on genome sequences have both flexibility and specificity, which would be ideal probes for fluorescence in situ hybridization (FISH) analysis of genome structure. In this study, the bulked oligos of the two arms of chromosome 7 of cotton were developed based on the genome sequence of Gossypium raimondii (DD, 2n=2×=26), and each arm contains 12,544 oligos. Chromosome 7 was easily identified in both D genome and AD genome cotton species using the bulked chromosome-specific painting probes. Together with 45S rDNA probe, the chromosome-specific painting probe was also successfully used to correct the chromosomal localization of 45S rDNA in G. raimondii. The study reveals that bulked oligos specific to a chromosome is a useful tool for chromosome painting in cotton.